V.2 - "Sarngadharan, M. (ed.)" (New Delhi, 2006)
Business environment in India is changing fast, bringing new opportunities as well as posing challenges. Economic liberalisation and globalisation have created keen interest in foreign investors, resulting in comfortable foreign currency reserves, stability of Indian Rupee, vibrant stock market and expanding financial and services sector. However, the operations of multinational corporations and policies of WTO pose threats to some sectors of the Indian economy, especially to small and medium industries and agriculture. The present work in two volumes contains articles on issues crucial to the contemporary business and economy in India. The book in two volumes contains 25 articles which have been organised into seven theme titles.
Keywords: Economic development